FEATURES OF MECHANICS DESTRUCTION TRIBOUNITS AT DIFFICULT DYNAMIC LOADING - Tsyganov, V.V. (Eurasian Physical Technical Journal, 2023)
The mechanics of contact destruction tribounits at a friction in the conditions of difficult dynamic loading is considered. Possibility of mathematical description of complex damage knots friction is shown, intensities of wear taking into account the features of forming superficial layer at a contact. Methodology of calculation superficial durability and longevity of tribounits is presented and the examples of practical estimation of this interdependence are shown. The model of destruction surface at a friction with a different dynamic loading is offered, methods of estimation wearproofness on the change of the structural state of superficial layer by a tribospectral method and the electron work function.